EVALUATION OF HEPATOPROTECTIVE (PREVENTIVE & CURATIVE) ACTIVITY OF LEAVES EXTRACT OF ROSA CENTIFOLIA ON EXPERIMENTAL ANIMAL MODELS - Maheshwara Rao, K. Uma; Reddy, R.V. Ramanarayana; Vangoori, Yakaiah; Sundharam, J. Mohana (Asian Journal of Pharmaceutical and Clinical Research, 2014)
OBJECTIVE: The experimental study was designed to evaluate the hepatoprotective (preventive and curative) activity of Ethanolic extract of leaves of ROSA CENTIFOLIA (RC) in experimental animals (rats). METHODS: In both models (preventive and curative) the Liver was damaged by giving Carbon tetra chloride (CCl4)-1ml/kg-p.o. Increased in the levels of biochemical markers of Hepatic damage like SGPT, SGOT, ALP and BILURUBIN (TB). Treatment with extract of ROSA CENTIFOLIA (300mg, 600mg/kg) in preventive model for 7 days and then from 7 to 14 days in curative model. The extract of RC was effectively reduced the high levels of enzymes in the plasma in preventive than curative models in the dose dependent manner. The enzyme level reduction in serum was considered as Hepatoprotective property of RC. Pathological changes like centribular necrosis and vacuolization were observed in CCl4 treated rats, the same pathological changes were not observed in groups treated with RC and Silymarin (100mg/kg/day). CONCLUSION: The Ethanolic extract of RC has shown good hepatoprotective activity in preventive than curative research models against CCl4 induced hepatotoxicity in rats. Key words: Carbon tetrachloride, Silymarin, ROSA CENTIFOLIA, Hepatoprotection